Effect of Various Coolant Mass Flow Rates on Sealing Effectiveness of Turbine Blade Rim Seal at First Stage Gas Turbine Experimental Facility - Seok Min Choi; Seungyeong Choi; Hyung Hee Cho (Energies, 2020)
The appropriate coolant mass flow of turbine blade rim seal has become an important issue as turbine blades are exposed to increasingly higher thermal load owing to increased turbine inlet temperature. If the coolant is deficient, hot gas ingresses to the rim seal, or if sufficient, the efficiency of turbine decreases. Therefore, we analyzed sealing effectiveness of rim seal derive appropriate coolant mass flow rate at various conditions. The experimental facility was modified from one designed for an aero-engine gas turbine. Rotational Reynolds number varied from 3 <semantics>×</semantics> 105 to 5 <semantics>×</semantics> 105 based on rotational speed. Pressure was measured at various locations in the shroud, endwall, and rim seal. CO2 concentration was measured at various rim seal locations to analyze sealing effectiveness. Measured results showed that 1.35% coolant mass flow rate of rim seal exhibited a little ingress effect, whereas lower coolant mass flow rates exhibited higher ingress effect. A predicted correlation for sealing effectiveness of rim seal was derived at various rotational Reynolds number and coolant mass flow rate. The correlation will be useful for turbine cooling design, helping to predict sealing effectiveness of rim seals during preliminary design processes for new gas turbines.